2013
DOI: 10.1089/jayao.2012.0026
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Concordance in Reporting for Secondhand Smoke Exposure among Adolescents Undergoing Treatment for Cancer and Their Parents

Abstract: Few studies have examined adolescent reporting accuracy for secondhand smoke exposure (SHSe), and never for youth with cancer. SHSe reporting from adolescents being treated for cancer (M age = 14.92 years, SD = 1.67) was examined against parent/guardian reports and urine cotinine among 42 adolescent-parent dyads. Number of days in hospital-based lodgings prior to assessment emerged as the strongest predictor of urine cotinine (b = -0.46, p = 0.003) and adolescent SHSe reporting significantly predicted urine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Prior research has found that participants provide more accurate responses if they are asked to recall SHS exposure occurring within the home or personal vehicles 23 . Alternatively, adolescents are less accurate in reporting the duration of exposure 24 . Over-reporting may occur when respondents conflate SHS exposure with thirdhand smoke exposure (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has found that participants provide more accurate responses if they are asked to recall SHS exposure occurring within the home or personal vehicles 23 . Alternatively, adolescents are less accurate in reporting the duration of exposure 24 . Over-reporting may occur when respondents conflate SHS exposure with thirdhand smoke exposure (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Regular SHS exposure during adolescence can affect cardiovascular health into adulthood, potentially through negative effects that SHS has on diet, activity level, and percent body fat 27 . As adolescents grow older, they will gain more autonomy over their exposure to SHS 24 and there is some evidence to suggest that interventions focused on informing adolescents how to avoid SHS exposure may help to reduce SHS exposure 28 . However, by focusing interventions solely on adolescents, who have limited capacity to control their outside environments, we miss out on addressing other potentially relevant causes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, interventions geared toward parents of children being treated for cancer may have a more pronounced effect on parents with younger children. While it is possible that the results are attributable to methodological confounds (ie, parents of adolescents are unable to reliably estimate change in their child's exposure to SHS), this is unlikely as parents of adolescents have shown to be accurate reporters of their child's SHSe both in the home and in the car (McDermott, Nicholson, & Tyc, 2013). Alternatively, it may be that little change in adolescent exposure was demonstrated because parents have fewer opportunities to effect change in their teen's exposure to SHS.…”
Section: Discussionmentioning
confidence: 99%